Mathematics teachers' epistemological beliefs and technology acceptance in emergency remote teaching during the Covid-19 pandemic - Erol, Rumeysa. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2022., 2022)
This explanatory sequential mixed-method study examined middle school mathematics teachers’ emergency remote teaching (ERT) experiences in the Covid-19 pandemic in terms of their mathematics-oriented epistemological beliefs and technology acceptance levels. Quantitative data collected through Mathematics Oriented Epistemological Beliefs Scale (MOEBS) and Technology Acceptance Measure for Teachers Scale (T-TAM). Data from both scales are used to form four case groups. Participants (n=39) are invited to interviews based on their case groups. Qualitative data collected through semi-structured interviews and Concerns Based Adoption Model (CBAM) is used as a framework while collecting and analyzing the interview data. The results indicated that there is a positive but not statistically significant correlation between the mathematics- oriented epistemological beliefs and technology acceptance levels of middle school mathematics teachers. It is shown that teachers’ concerns about ERT practice are coherent with their MOEBS and T-TAM scores. Addition to concerns, teachers’ needs are mentioned to guide in-service training programs such crisis and future applications.
Keywords: Web-based instruction.; COVID-19 (Disease) -- Social aspects.; Mathematics -- Study and teaching.